Comparison of the Effects of Leuprolide Acetate and Dienogest on Endometrioma Size at Ulin Hospital Banjarmasin for the Period of January-December 2022 - Joyce Joyce; Iwan Darma Putra; Hardyan Sauqi; Yenni Chandra; Yakob Togar (Lambung Mangkurat University, 2023)
Endometrioma is a type of cyst formed when endometrial tissue grows on the ovarian epithelium. Leuprolide acetate and dienogest are the most frequently used endometrioma therapies and are included in the drugs covered by health insurance in Indonesia. This study aims to compare changes in endometrioma size after the administration of leuprolide acetate and dienogest for 6 months. This study used an analytical observational method with a pre and post design approach in endometrioma sufferers aged 18-45 years who sought treatment at the Obstetrics and Gynecology Polyclinic at Ulin Banjarmasin Regional Hospital for the period of January-December 2022. Women with endometrioma were evaluated for its endometrioma size before and after the administration of leuprolide acetate or dienogest therapy for 6 months using ultrasound examination. The number of samples obtained is 30 women each who received leuprolide acetate or dienogest therapy. The average change in endometrioma size in the dienogest group was 2.0247 cm, while in the leuprolide acetate group was 1.5083 cm. However, the results of statistical analysis showed no significant difference in endometrioma size between the two treatment groups (P > 0.05). Based on the research results, it can be concluded that the administration of leuprolide or dienogest does not make a difference in the size of the endometrioma.